Visualising the Psyche: Perspectives on mental health in the medium of comics - Solomon, Tayla Shan (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
The field of Psychology is constantly shifting in its understanding of mental health. Scholars have been critiquing Psychology's narrow perspective of what constitutes 'normal'. Many dealing with mental health issues fear that they will be misunderstood and are confronted with systems and institutions that they find unempathetic. This mini-thesis conceptualises creative empathy as a solution to these problems. It is based on the idea that every experience is unique and therefore cannot be wholly understood without engaging in an imaginative process. The appropriateness of the comics medium as a tool for promoting this strategy is explored with a focus on the use of visual imagery to tell stories of distressing experiences. It looks at Tayla Shan Solomon's The Adventures of Apparently-Anyone-Can-Do-It-If-TheyJust-Try Bug! (2019), Art Spiegelman's Maus (I & II) (1986), Joe Kelly and JM Ken Niimura's I Kill Giants (2011), and Allie Brosh's Hyperbole and a Half: unfortunate situations, flawed coping mechanisms, mayhem, and other things that happened (2013). This mini-thesis analyses various techniques employed by comics artists to create compelling stories of idiosyncratic experiences, including the use of symbolic imagery and framing.
Keywords: Spiegelman, Art -- Maus; Kelly, Joe, 1971- -- I kill giants; Niimura, J M Ken -- I kill giants; Brosh, Allie -- Hyperbole and a half; Comic books, strips, etc. -- Psychological aspects; Comic books, stripa, etc. -- Therapeutic use